Study of Seismic Hazard Level Based on Microtremor Measurement Analysis in Koto Tangah District, Padang City - Emriska, Vellya Ramadhani; Syafriani, -; Fauzi, Ahmad; Dwiridal, Letmi (Department of Physics – Universitas Negeri Padang UNP, 2024)
The city of Padang is tectonically one of the areas with very high seismic activity in Indonesia. Therefore, we conduct a study to determine the level of seismic hazard using analysis of microtremor measurements in the sub-district of Koto Tangah, Padang City, as well as micro-zoning the distribution of the dominant frequency value, amplification value, dominant period, and seismic vulnerability index. The type of research is descriptive research, namely by taking microtremor data using a sysmatrack MAE seismograph and S3S sensor in Koto Tangah sub-district, Padang city. Microtremor data processing uses geopsy software to remove noise data and see the dominant frequency and amplification values. From the results obtained, the gypsy software then made a contour mapping of its value using the surfer 13 application and microzonation mapping. The results obtained from this study in the Koto Tangah sub-district, Padang City, are areas that are vulnerable to seismic hazards whose data can be seen from the distribution of the micro zonation value of dominant frequency (f0), amplification factor (A0), dominant period (T0), and seismic vulnerability index value. (Kg) is included in the medium to high category due to the influence of underground geology.